Increasing γ-Aminobutyric Acid in Mixed Germinated Brown Rice Via Electron Beam Irradiation - Prakhongsil, Panchalee; Sajjabut, Surasak; Pewlong, Wachiraporn; Khemthong, Khemruji; Eamsiri, Jarurattana; Picha, Roppon; Thamrongsiripak, Nuatawan (Trends in Sciences, 2024)
Germinated brown rice (GBR) is considered a functional food due to its rich health promoting bioactive compounds such as γ-aminobutyric acid (GABA), γ-oryzanol, phenolics, and antioxidants. In this study, different germinated brown rice varieties were treated with electron beam irradiation (EBI) and x-ray irradiation to assess the effects on these compounds. Food irradiation technology endorsed by the US-FDA and WHO for improving food safety and extending shelf life was utilized. Germinated black fragrant brown rice (Hom Nil brown rice, Oryza sativa L.), and germinated brown rice (GBR) mixed with 3 varieties of brown rice (Thai Hom Mali brown rice, red cargo brown rice, and black fragrant brown rice) were treated with EBI and x-ray irradiation at a dose of 1 kGy, energy levels of 10 and 5 MeV, respectively. The results showed that EBI at the specified dose could significantly increase GABA content in a mixed GBR sample from 3.76 mg/100 g (dried weight) in a non-irradiated sample to 6.44 mg/100 g (dried weight) in an EBI sample, which was a 1.7 fold increase. Moreover, both irradiation methods did not impact any other health promoting compounds such as γ-oryzanol, total phenolic content, or antioxidant activity. However, x-ray irradiation decreased anthocyanin activity in germinated black fragrant brown rice. The Hunter Lab system was used to determine color characteristics. The results showed that EBI slightly increased the yellowness value of a mixed GBR sample. In addition, EBI and x-ray irradiations can reduce microbial contamination of total aerobic plate count and total yeast and mold count in both GBR samples to low levels of 1.30 102 1.30 10 and < 10 1.8 10 CFU/g, respectively. The results demonstrated that EBI can improve the nutritional quality and enhance consumer food safety in GBR products. HIGHLIGHTS Electron beam irradiation (EBI) and x-irradiation were applied to germinated brown rice (GBR) in both single and mixed formulas for the purpose of enhancing health promoting compounds. A low dose of electron beam irradiation (EBI) significantly increased the gamma aminobutyric acid (GABA) content in mixed germinated brown rice, which includes Thai Hom Mali brown rice (Oryza sativa), red cargo brown rice, and black fragrant brown rice compared to the non-irradiated sample. The highest levels of health promoting compounds were detected in a single formula of germinated black fragrant brown rice. Both types of irradiation did not alter the GABA content or antioxidant activities of the GBR sample. However, anthocyanin activity was decreased by x-ray irradiation. All GBR samples showed low levels of microbial contamination. GRAPHICAL ABSTRACT